Processing of Carbon Disulfide at KRC for Safe Disposal (Chemical Engineering Research Bulletin, 2009)
The Karnaphuli Rayon Complex (KRC) was permanently closed down in January 1997 by leaving behind about 180 tons of Carbon Disulfide (CS2) in sixteen storage tanks at various locations of KRC and CS2 plant including in some vessels of CS2 plant itself. An incineration facility was planned, designed, constructed, commissioned and operated to dispose all CS2 left behind. The facility used some of the facilities of the closed Sulfuric Acid Plant (30 tpd) which was closed in December 2002. The incineration facility was commissioned on April 1, 2008 and the processing of CS2 was completed on September 16, 2008. Catastrophic failure of the tanks was inevitable and matter of time. Such failure would have led to events worse than Bhopal causing deaths, fatal injuries and immediate environmental damage of all types. This is a success story of local engineering endeavor from laboratory to industry.Keywords: Carbon Disulfide, KRC, Incineration, Safe DisposalDOI = 10.3329/cerb.v13i1.3207 Chemical Engineering Research Bulletin 13 (2009) 25-28